2021
DOI: 10.1021/acs.est.1c06244
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Active Sites to Generated Reactive Species and Degradation Routes of Organics in Peroxymonosulfate Activation by Co-Loaded Carbon

Abstract: Peroxymonosulfate (PMS)-based advanced oxidation processes (PMS-AOPs) as an efficient strategy for organic degradation are highly dependent on catalyst design and structured active sites. However, the identification of the active sites and their relationship with reaction mechanisms for organic degradation are not fully understood for a composite catalyst due to the complex structure. Herein, we developed a family of Co encapsulated in Ndoped carbons (Co-PCN) with tailored types and contents of active sites vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 280 publications
(60 citation statements)
references
References 88 publications
2
57
1
Order By: Relevance
“…With the structure change from CoÀ N 4 moiety to CoÀ N 3 O 1 moiety, the inhibition of L-histidine increased from 35.28 % to 63.05 %, while the inhibition of TBA decreased from 78.71 % to 6.73 % (Figure 3e). Note that other factors such as the interaction between PMS and L-histidine, [33] PMS self-decomposition, [31] electron transfer [4,34] et al could have an impact on the degradation process. Throughout a series of experiment under different conditions (Figure S17 and S18), we further identified that 1 O 2 were dominant radicals and the origin relied on PMS activation by CoÀ N 3 O 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…With the structure change from CoÀ N 4 moiety to CoÀ N 3 O 1 moiety, the inhibition of L-histidine increased from 35.28 % to 63.05 %, while the inhibition of TBA decreased from 78.71 % to 6.73 % (Figure 3e). Note that other factors such as the interaction between PMS and L-histidine, [33] PMS self-decomposition, [31] electron transfer [4,34] et al could have an impact on the degradation process. Throughout a series of experiment under different conditions (Figure S17 and S18), we further identified that 1 O 2 were dominant radicals and the origin relied on PMS activation by CoÀ N 3 O 1.…”
Section: Resultsmentioning
confidence: 99%
“…With the structure change from Co−N 4 moiety to Co−N 3 O 1 moiety, the inhibition of L‐histidine increased from 35.28 % to 63.05 %, while the inhibition of TBA decreased from 78.71 % to 6.73 % (Figure 3e). Note that other factors such as the interaction between PMS and L‐histidine, [33] PMS self‐decomposition, [31] electron transfer [4, 34] et al. could have an impact on the degradation process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations